If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -55 = 4x + 5 Reorder the terms: -55 + 5y = 4x + 5 Reorder the terms: -55 + 5y = 5 + 4x Solving -55 + 5y = 5 + 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + 5y = 5 + 55 + 4x Combine like terms: -55 + 55 = 0 0 + 5y = 5 + 55 + 4x 5y = 5 + 55 + 4x Combine like terms: 5 + 55 = 60 5y = 60 + 4x Divide each side by '5'. y = 12 + 0.8x Simplifying y = 12 + 0.8x
| X^2-2x+3x-27=105 | | Y-(-3)=-4(x-1) | | 2x-7+2x-5+x-1=(3x-11)2+2(x-3) | | -2x+20=14 | | x+38=90 | | 3(g-3)=24 | | 5+.50y=1.0y+0 | | 6x-18=5x+8 | | C-62.3=20186.7 | | 8a-2a-10=2a-2 | | 7-3x=6x+34 | | 15-2g=3g | | -5x+(3x)(3x)-3x+100-125=0 | | 15x+6=60+6 | | f+7-3f+5f=13 | | 5(3x)=12(5) | | 2x+x=57 | | 8(4r-1)-2r=10r+92 | | 2e+9-4e=10+1 | | (6x+2)+(-7x+6)= | | .92y+2.4=y | | 3x+5+2x+20+3x-5=180 | | 8(m-3)=24 | | 30d^2+48d+18=0 | | 21=3x(4*5+x) | | 3(2x+5)-2(4x+1)=-5(x+3)-2 | | 5-3(y-4)=-2 | | 5x-13=4x-14 | | 27.5=2y-35 | | 2x(5-x)(3x-4)(x+2)=0 | | 32.23=5.3x | | 2y-35=2y-35 |